Triterpenic azines, a new class of compounds with selective cytotoxicity to leukemia cells CCRF-CEM - Pokorny, Jan; Krajcovicova, Sona; Hajduch, Marian; Holoubek, Martin; Gurska, Sona; Dzubak, Petr; Volna, Tereza; Popa, Igor; Urban, Milan (Future medicinal chemistry, 2018)
AIM: From betulinic acid (1a), we synthesized 30-oxobetulinic acid (2a) that is highly cytotoxic against many cancer cell lines; however, its generic toxicity is the main obstacle in further development as cytostatic. Methodology & results: From 2a, we prepared a new class of compounds - nonsymmetrical azines and tested their in vitro cytotoxicity. All new azines with a free 28-COOH group (4a-4e) were highly and selectively cytotoxic against the T-lymphoblastic leukemia cell line CCRF-CEM and exhibited dose-dependent inhibition of RNA and DNA synthesis and other cell-cycle alterations, including the M-phase block. CONCLUSION: The potential use of azines (4a-4e) in drug development focused on hematological cancers is significantly higher than that of previously studied acids 1a and 2a.
Keywords: molekulární konformace; Molecular Conformation; Drug Screening Assays, Antitumor; Antineoplastic Agents, Phytogenic; Humans; fytogenní protinádorové látky; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Triterpenes; lidé; proliferace buněk; hydrazone; buněčné linie; Cell Line; betulinic acid; triterpeny; Cell Proliferation; screeningové testy protinádorových léčiv; vztah mezi dávkou a účinkem léčiva; cytotoxicity; Hydrazines; hydraziny